2001
DOI: 10.1046/j.1365-3040.2001.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of intraspecific responses to UV‐B radiation in white clover (Trifolium repensL.)

Abstract: White clover (Trifolium repens L.) is experiencing increased levels of ultraviolet-B (UV-B) radiation in temperate pastures due to the depletion of the stratospheric ozone layer. Based on 17 morphological, morphogenetic and physiological attributes, this study analysed the consequences of enhanced UV-B on 26 white clover populations using principal components analysis (PCA). After 18 d of exposure to 13·3 kJ m -2 d -1 UV-B in controlled environments, UV-B significantly decreased above-ground and below-ground p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 47 publications
6
41
0
Order By: Relevance
“…In contrast, compared with NA, +UVB caused significant inhibition of photosynthesis (A), total leaf area and biomass accumulation in the low-altitude population (Tables 1, 2), paralleling the significant reduction in antioxidant content (Asa) (Tables 2, 3), which further led to lower tolerance to +UVB. Previous studies also documented that plant populations from high UV-B habitats were more tolerant to enhanced UV-B (Hofmann et al 2001;Ren et al 2006), and our study showed that the intraspecific differences of plant responses to UV-B were closely related with plant characteristics of leaf morphology, antioxidant capacity and physiological modifications.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, compared with NA, +UVB caused significant inhibition of photosynthesis (A), total leaf area and biomass accumulation in the low-altitude population (Tables 1, 2), paralleling the significant reduction in antioxidant content (Asa) (Tables 2, 3), which further led to lower tolerance to +UVB. Previous studies also documented that plant populations from high UV-B habitats were more tolerant to enhanced UV-B (Hofmann et al 2001;Ren et al 2006), and our study showed that the intraspecific differences of plant responses to UV-B were closely related with plant characteristics of leaf morphology, antioxidant capacity and physiological modifications.…”
Section: Discussionsupporting
confidence: 79%
“…1b, 2). Previous studies on Arabidopsis thaliana, white clover and tartary buckwheat indicated that UV-B induced changes in plant traits were negatively correlated with their constitutive values under control conditions (Cooley et al 2001;Hofmann et al 2001, Yao et al 2007. We also observed that the low constitutive values in terms of growth and yield-related parameters in the high elevation cultivar remained less affected than lowland cultivars.…”
Section: Discussionsupporting
confidence: 65%
“…However, impaired SOD activity and reduced Asa concentration under high level of UV-B radiation suggested that the plants are unable to cope with high stress intensity and that oxidative damage could be, at least partly, responsible for plant growth inhibition and ultimate yield decrease (Jansen et al 1998). Plant populations originating from high UV-B habitats are supposed to be more tolerant to UV-B radiation than those from low UV-B origin (Teramura and Sullivan 1991;Yang et al 2005) since the high elevation plants should have selected adaptative strategies (Hofmann et al 2001). Our results showed that the high elevation cultivar exhibits a high adaptability to its original ambient UV-B radiation (+5.0 kJ m -2 UV-B) while the lowland cultivars would suffer from marked reductions in growth, final yield and dry matter accumulation if they are cultivated in Qinghai-Tibet plateau region.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate assessment was further used to explore whether constitutive features could be linked to the overall O 3 responsiveness of the white clover clones. Similar multivariate analytical approaches have been used in other investigations on stress sensitivity/tolerance (Somersalo et al, 1998;Hofmann et al, 2001). However, there is a general shortage of multivariate investigations in the examination of O 3 responses in plants.…”
Section: Introductionmentioning
confidence: 95%